Designers' guide to Eurocode 1 : actions on buildings : EN1991-1-1 and -1-3 to -1-7 - Gulvanessian, H. (Thomas Telford, 2009)
The design process of a bridge includes several steps. One of the major steps is the determination of actions & combinations of actions. These actions are imposed loads due to traffic climatic actions, actions due to water or soil subsidence construction loads & accidental actions.
"Eurocodes Expert ... a new ICE and Thomas Telford initiative set up to assist in creating a greater awareness of the impact and implementation of the Eurocodes within the UK construction industry"--Title page verso
Keywords: Structural design -- Standards -- European Union countries.; Buildings -- Standards -- European Union countries.; Eurocodes (Standards); elektronické knihy; electronic books